THE INFLUENCE OF COMMUNICATION WITH PETS ON THE EMOTIONAL STATE OF CHILDREN - Reymov Mukhamedali Kengesbaevich; Yakupbayeva Munira Karimbay qizi; Berdikhanova Gulnara Nurlibaevna; Kendjayeva Dilfuza Raxmetovna (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article considers the influence of pets on the development of children.